Seawater carbonate chemistry and skeletal morphometricss of hybrid coral recruits - Meyers, Luka; Shaw, Jeremy; Clode, Peta; Harrison, Peter; van Oppen, Madeleine J H; Chan, Wing Yan (PANGAEA, 2025)
Using high-resolution 3D X-ray microscopy, this study aims to quantify skeletal parameters (e.g. length, diameter, surface area and volume) and examine skeletal deformity of purebred and interspecifc hybrid Acropora coral recruits previously generated via experimental crossing of Acropora cf. kenti and Acropora loripes. When tested under predicted ambient and mid-century conditions, hybrid ofspring were ftter than at least one of the parental purebreds, with survival and size being similar to, or exceeding that of the maternal parent. This study aims to determine whether the skeletal structure of these 7-month-old hybrid and purebred recruits were diferentially afected by predicted mid-century warming and acidifcation conditions. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were extracted from tables in the related paper (see Related to) by the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-04-22.
Keywords: Acropora loripes; Acropora tenuis; Animalia; Benthic animals; Benthos; Bottles or small containers/Aquaria (<20 L); Cnidaria; Coast and continental shelf; Growth/Morphology; Laboratory experiment; South Pacific; Species interaction; Temperature; Tropical